PENGARUH PENGUNAAN TWO STAY TWO STRAY TERHADAP HASIL BELAJAR DALAM PEMBELAJARAN IPS DI SD - Fitria, Fitria; Sugiyono, Sugiyono; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to analyze the effect of the use of the two stay two stray method for learning outcomes in social studies subjects V grade SD Negeri 18 West Pontianak. The research method used is the experimental method of Quasi Experimental Design type Nonequivalent Control Group Design. The population in this study were all fifth grade students with a total of 95 students. The sample selection is done by purposive sampling and the experimental class is VC (29 students) and the VB control class (31 students). Data collection tool in the form of a test with a number of 50 multiple choice questions. Based on the results of statistical calculations obtained an average of 88.76 experimental class final tests and 79.60 control class. The results of the t-test calculation Polled Variance one-sided test obtained t-count 3.677 for dk = 52 and Î± = 5% obtained t-table 1.672 which means t-count Ëƒ t-table, then Ha is accepted. This shows there are differences in student learning outcomes in the experimental class with the control class. The results of the calculation of the effect size of 1.0327 (high criteria). The conclusion of this study is that there is an influence of the useÂ two stay two stray method.Â Keywords: Influence, Two Stay Two Stray, Learning Outcomes